2022
DOI: 10.1183/23120541.00571-2021
|View full text |Cite
|
Sign up to set email alerts
|

Vascular remodelling in idiopathic pulmonary fibrosis patients and its detrimental effect on lung physiology: potential role of endothelial-to-mesenchymal transition

Abstract: BackgroundIPF is a progressive, irreversible fibrotic interstitial lung disease. We performed size-based quantitation of pulmonary arterial remodelling in IPF, examined the role of EndMT and effects on lung physiology.MethodsResected lung tissues from 11 normal controls (NC), and 13 IPF patients, were differentially stained using the Movat Pentachrome technique. Size-based classification for pulmonary arteries was conducted in NC and IPF tissues. For each pulmonary artery, arterial size, luminal diameter, thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Archana et al. have shown that EndMT markers(N-cadherin, S100A4, and vimentin) are increased in the arterial layers (intima, media, and adventitia) of IPF patients ( 33 ). Similarly, during the EndMT process, active ECs express adhesion molecules, such as intercellular adhesion molecule-1 ( ICAM-1 ) and vascular cell adhesion molecule-1 ( VCAM-1 ), which enhance EndMT formation in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Archana et al. have shown that EndMT markers(N-cadherin, S100A4, and vimentin) are increased in the arterial layers (intima, media, and adventitia) of IPF patients ( 33 ). Similarly, during the EndMT process, active ECs express adhesion molecules, such as intercellular adhesion molecule-1 ( ICAM-1 ) and vascular cell adhesion molecule-1 ( VCAM-1 ), which enhance EndMT formation in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Movat's pentachrome staining was performed in tissue sections from all groups following our previously published work [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…First, maximum external diameter (end to end of adventitia) and luminal diameter (end to end of inner intima) were measured ( figure 1a ). Next, arteries with a maximum diameter between 100 µm and 1000 µm were segregated into three groups, with arteries measuring 100–299 µm classed as small, 300–499 µm as medium and 500–999 µm as large ( figure 1b ) [ 14 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid EMT has also been suggested in COPD and patients with IPF [ 52 ]. Endothelial-to-mesenchymal transition (EndMT) is a similar process to EMT, and these drugs may have similar effects on EndMT as well, but further work is warranted [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Oral corticosteroids are yet to be tested for their efficacy for such effects.…”
mentioning
confidence: 99%